Management and Prevention of Nasal Schistosomosis in a She-Buffalo: Clinical Insights - Vutharamalluru, Gnani Charitha; Pathalota, Gayathri; Badvel, Surendra; Pothanaboina, Guru Vishnu; N, Jagadeeswar Reddy (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Nasal schistosomosis (Snoring disease) is a snail born trematode infection of domestic and wild ruminants caused by Schistosoma nasale (Chandra Sekhar et al., 2021). This pathogen primarily affects cattle and buffaloes leading to significant economic losses in livestock dependent areas across Asia and Africa. Serious outbreaks of this disease among cattle and buffaloes have been reported in certain regions of India, viz., Tamil Nadu, Karnataka, Kerala, West Bengal (Sumanth et al., 2004; Agarwal, 2012; Ravindran and Kumar, 2012). Fresh water snail belonging to genus Indoplanorbis acts as intermediate host (Liu, 2010). Primary mode of transmission is through skin penetration when free swimming larval stage cercaria comes in contact with the ruminants in contaminated water bodies. Upon entering the definitive host, the parasite primarily affects nasal blood vessels. The main pathogenic effects are associated with the eggs that trigger granuloma formation through release of antigens that stimulate the host immune system, leading to a chronic inflammatory response in the nasal mucosa that may occlude the nasal passage.